PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR KIMIA - Sri Winarti (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
The aim of this research was to determnine the steps of applying peer tutoring in increasing student motivation and learning outcomes, applying peer tutoring learning steps in increasing student motivation and learning outcomes. This research is a class action research (CAR) consisting of two cycles, and each cycle consists of three meetings. These subjects of this study were students of class X MIPA1 of 1 Senior High School Turi consisting of 10 male students and 24 female students. This research was conducted in August – November 2019. Data collection techniques were carried out by observation, written tets, and qustionnaires. Data analysis technique is description by comparing the results of actions with indicator of research targets. The research procedure starts from the planning, implementation, observation, to reflection. Indicators of research success are 85% of students have high motivation and at least 85% of students score of Minimum Master Criterion. The results showed that the peer tutoring method in learning could increase motivation and student learning outcomes. Student motivation reached 91,25% at the end of this cycle, and the end of the second cycle it reached 99,06%. While student learning outcomes reached 60,61% at the end of the first cycle and at the end of the second cycle it reached 90,63%. Thus, the peer tutoring method can be said to be successful in increasing student motivation and learning outcomes.